PENERAPAN SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN PRIORITAS LOKASI PEMASARAN PADA PT. ASKRINDO CABANG MEDAN MENGGUNAKAN METODE AHP DAN PROMETHEE - Zulfani, Fathania; Suryamen, Haris; Wahyuni, Ullya Mega (ITP Press, 2024)
P.T. (Persero) Credit Insurance Indonesia is one of the state-owned enterprises (SOEs) that engage in insurance or guarantees. The existence of PT Asuransi Kredit Indonesia (Askrindo), which is one of the state-owned enterprises (SOE), has always been associated with the success of the economic development of the Nation and the Republic of Indonesia. Marketing plays a major role in the company, including PT Askrindo; However, determining strategic marketing location priorities requires careful analysis of drivers to avoid both tangible and intangible losses. The purpose of this research is to develop a decision support system (DSS) using a combination of the analytical hierarchy process (AHP) and the PROMETHEE method, which can be considered in the selection of priority marketing positions based on predetermined standard . Using AHP and PROMETHEE methods to prioritize marketing locations with multiple location alternatives can aid decision-making activities, thereby improving a company's efficiency in making informed decisions. Having a decision support system, it can serve as a solution to help the branch of PT Askrindo in Medan to make decisions in choosing the best priority marketing positions.